PENGARUH PENAMBAHAN SUSU SKIM DALAM PEMBUATAN MINUMAN PROBIOTIK SUSU JAGUNG (Zea mays L.) MENGGUNAKAN KULTUR Lactobacillus acidophilus - FADRO '; RASWEN EFENDI '; FAJAR RESTUHADI ' (Jurnal Sagu, 2015)
ABSTRACTCorn milk is a local food that can be made to probiotic drink. Probiotic drink is a functional food that isprocessed through a fermentation. The production of corn milk probiotic drink using lactic acid bacteria(LAB). Lactic acid bacteria (LAB) requires nutrients for its growth. This research using skim milk as a sourceof nutrients for the lactic acid bacteria (LAB). The purpose of this research is to obtain the skim milkconcentration to produce best quality of corn milk probiotic drink. This research using a completelyrandomized design (CRD) with skim milk concentration (5 , 7, 9, 11 dan 13 % (w/v)). Analysis of variance(ANOVA) showed the skim milk concentration had a significant effect on the degree of acidity (pH), total oflactic acids, total of lactic acid bacteria (LAB), content of protein and total of solids. The best corn milkprobiotic drink is produced by addition of skim milk amount 7% (w/v), pH 4,88 , total of lactit acid 0,31%,total of lactic acid bacteria (LAB) 9.55 log CFU/ml, content of protein 2,12% and total of solids 18,42 %.Key words: lactic acid bacteria (LAB), skim milk and corn milk probiotic drink